2016
DOI: 10.1016/j.bbamem.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Branched phospholipids render lipid vesicles more susceptible to membrane-active peptides

Abstract: Iso- and anteiso-branched lipids are abundant in the cytoplasmic membranes of bacteria. Their function is assumed to be similar to that of unsaturated lipids in other organisms – to maintain the membrane in a fluid state. However, the presence of terminally branched membrane lipids is likely to impact other membrane properties as well. For instance, lipid acyl chain structure has been shown to influence the activity of antimicrobial peptides. Moreover, the development of resistance to antimicrobial agents in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Zones of inhibition were markedly lower in both strains on serum agar for rifampicin, chloramphenicol, and tetracycline. However, membrane permeability studies clearly need to be done in a more simplified system such as lipid vesicles of defined fatty acid composition [58] to simplify the interpretation of any differences observed. Cells grown in serum had higher hemolytic activity, and MH broth and serum- grown cells had lower autolytic activities than cells grown in the other media (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Zones of inhibition were markedly lower in both strains on serum agar for rifampicin, chloramphenicol, and tetracycline. However, membrane permeability studies clearly need to be done in a more simplified system such as lipid vesicles of defined fatty acid composition [58] to simplify the interpretation of any differences observed. Cells grown in serum had higher hemolytic activity, and MH broth and serum- grown cells had lower autolytic activities than cells grown in the other media (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, phosphatidylethanolamine (PE) is also present in Gram-positive cytoplasmic membranes. Moreover, phospholipids of Gram-positive species are characterized by a high content of branched-fatty acids, which were shown to influence the activity of AMPs [ 91 ]. The main physicochemical properties of these major bacterial phospholipids are summarized in Table 3 .…”
Section: Architecture Of Gram-positive Cell Envelopesmentioning
confidence: 99%
“…Further, other dicationic styryl probes such as di-4-ANEPPDHQ have been observed to flip-flop in model vesicles using SHG (67).The fact that we observe signatures of FM 4-64 flip-flop in S. aureus but not E. faecalis may also be explained by the differences in their membrane fluidity and phosopholipid head group charge. As discussed above, the membranes of S. aureus have more phospholipids with branched acyl chains than E. faecalis, and this has previously been shown to increase the membrane fluidity (51,52). Previous theoretical and experimental studies have both shown that increasing the fluidity of the different membranes being investigated was directly correlated with an increase in the flip-flop rate observed.…”
Section: Discussionmentioning
confidence: 85%
“…These differences in temperature response for the two bacterial species may be attributed to differences in the fatty acid tails of the phospholipids which are integral to establishing the degree of membrane fluidity. More fluidic membranes are typically composed of shorter acyl chains (50), along with chains that are branched or unsaturated (51,52). S. aureus is known to have a greater percentage of branched acyl chain structures in its lipidome in comparison to E. faecalis (4,48,49,53,54).…”
Section: Discussionmentioning
confidence: 99%